Inhibitory Effect of a Nucleotide Analog on Infectious Salmon Anemia Virus Infection - Spencer-Ossa, E; Sandino-Garcia, A; Rivas-Aravena, A; Tello-Reyes, M; Cortez-San Martin, M; Reyes-Lopez, F (American Society for Microbiology, 2011)
The infectious salmon anemia virus (ISAV), which belongs to the Orthomyxoviridae family, has been responsible for major losses in the salmon industry, with mortalities close to 100% in areas where Atlantic salmon (Salmo salar) is grown. This work studied the effect of ribavirin (1-?-D-ribofuranosyl-1,2,3-triazole-3-carbaxaide), a broad-spectrum antiviral compound with proven ability to inhibit the replicative cycle of the DNA and RNA viruses. The results show that ribavirin was able to inhibit the infectivity of ISAV in in vitro assays. In these assays, a significant inhibition of the replicative viral cycle was observed with a 50% inhibitory concentration (IC50) of 0.02 ?g/ml and an IC90 of 0.4 ?g/ml of ribavirin. After ribavirin treatment, viral proteins were not detectable and a reduction of viral mRNA association with ribosomes was observed. Ribavirin does not affect the levels of EF1a, nor its association with polysomes, suggesting that the inhibition of RNA synthesis occurs specifically for the virus mRNAs and not for cellular mRNAs. Moreover, ribavirin caused a significant reduction in genomic and viral RNA messenger levels. The study of the inhibitory mechanism showed that it was not reversed by the addition of guanosine. Furthermore, in vivo assays showed a reduction in the mortality of Salmo salar by more than 90% in fish infected with ISAV and treated with ribavirin without adverse effects. In fact, these results show that ribavirin is an antiviral that could be used to prevent ISAV replication either in vitro or in vivo. © 2011, American Society for Microbiology.